2019
DOI: 10.1186/s12889-019-7607-2
|View full text |Cite
|
Sign up to set email alerts
|

The short-term effects of air pollutants on influenza-like illness in Jinan, China

Abstract: Background There is valid evidence that air pollution is associated with respiratory disease. However, few studies have quantified the short-term effects of six air pollutants on influenza-like illness (ILI). This study explores the potential relationship between air pollutants and ILI in Jinan, China. Methods Daily data on the concentration of particulate matters < 2.5 μm (PM 2.5), particulate matters < 10 μm (PM10), sulfur di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
95
2
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(110 citation statements)
references
References 44 publications
9
95
2
4
Order By: Relevance
“…We believe PM 10 is also harmful respiratory tract to some extent as starts at 20 µm and beyond, PM is not able to penetrate below the trachea [31]. This might also explain our finding that PM 2.5 is more tightly correlated with the COVID-19 incidence than that of the PM 10 . The safety guideline concentration of PM 2.5 of PM 10 are 15 and 50 µg/m 3 by US EPA[32], respectively.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…We believe PM 10 is also harmful respiratory tract to some extent as starts at 20 µm and beyond, PM is not able to penetrate below the trachea [31]. This might also explain our finding that PM 2.5 is more tightly correlated with the COVID-19 incidence than that of the PM 10 . The safety guideline concentration of PM 2.5 of PM 10 are 15 and 50 µg/m 3 by US EPA[32], respectively.…”
Section: Discussionmentioning
confidence: 89%
“…It is speculated that the airborne air pollutants provide "condensation nuclei" for virus to attach. This hypothesis was supported by the studies based on the observation of influenza-PM2.5 correlation [10][11][12]. Although the COVID-19 is known to cause human-to-human transmission by infectious secretions [3], these secretions can be transferred in many different ways.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Historically, previous studies have shown that there is a positive correlation between PM2.5 and larger particulate sizes, and transmission of virus such as in uenza. [45] The Centres for Disease Control and Prevention (CDC) carried out a study which showed that the Sars-CoV-2 virus was able to remain viable for upto 72 hours on some surfaces (32) One could argue that the risk of transmission in the dental setting via aerosols is minor as the aerosol droplets may be entirely from the waterline. However when we look at a study on splatter and aerosol generated from an ultrasonic scaler without any coolant water used in vitro, there was still a substantial number of aerosol and splatter formed from small amounts of liquid placed at the operating site to simulate blood and saliva.…”
Section: Minimizing Aerosols and Splattermentioning
confidence: 99%
“…No correlation was found betweenvirus concentration and particulate matter as a function ofparticles diameter. Nevertheless, positive correlations betweenPM 2.5 and other respiratory viruses such as thein uenza virus have been reported 11 , emphasizing thepossibility of particulate matter as a transport carrier forSARS-CoV-2. PM 2.5 is ne solid aerosols with a particle diameterof ≤ 2.5 μm that is suspended in ambient air.…”
Section: Main Textmentioning
confidence: 99%